(untitled) (Comparative & International Education Series, 2021)
With the increase of international students studying abroad and concerns about the university admissions process being corrupted, one understudied issue is how international students are experiencing the application process. The largest group of international students that study in the United States come from mainland China, and the non-profit Beijing Overseas Study Service Association (BOSSA) estimates that there are over 4,000 study abroad agencies currently operating in Mainland China. However, these agencies often lack transparency and little information is known about the services provided to students and how these agencies operate. Drawing from my own personal experience working in the study abroad industry in mainland China, I plan to examine how study abroad agencies work, the ethical issues that sometimes go along with these agencies, and the roles that these agencies play in the journey of Chinese students who wish to study abroad.